The short-term distributional impact of COVID-19 in Malawi - Chimwemwe Magalasi (University of Essex, Institute for Social and Economic Research (ISER), 2021)
This study analyses the short-term distributional effects of COVID-19 on household incomes in Malawi. Growth is expected to fall due to the pandemic. The Malawi annual gross domestic product growth rate for 2020 has been revised downwards from 5.5% to 1.9%. According to the government of Malawi, unemployment in Malawi is expected to increase in 2020 compared to 2019 as companies begin to lay-off employees due to both demand and supply shocks. Our study investigates the impact of changes in employment due to the COVID-19 crisis on inequality and poverty using the recently developed tax-benefit microsimulation model for Malawi, MAMOD. In assessing the impact of the job losses, three employment shock scenarios are considered. Our study leverages on the novel High Frequency Phone Survey for COVID-19 that was implemented from June 2020 and the recently released Integrated Household Survey which was collected just before the COVID-19 crisis. We find that the poverty measured by headcount and poverty gap increases because of the COVID-19 outbreak. The pandemic has also worsened inequality as the Gini Coefficient rose. We further find that the corrective measures implemented the Emergency Cash Transfer, were able to subdue the impact of the crisis especially at the bottom of the income distribution.
Keywords: D31; E24; H24; 330; COVID-19; income distribution; poverty; fiscal policy; Malawi